Sustainable Development of the Modern Rural School as a System of Educational Environment under the Conditions of Globalization and Various Contradictions in Latvia - Katane, Irena (Acta Paedagogica Vilnensia, 2006)
The aim of this article is to describe research "The Evaluation Model of the Rural School as Educational Environment " and offer analysis and evaluation of results. The author investigated the sustainable development of rural school as educational environment in the today’s changing conditions from evolutional, structural and functional aspects. Results of empirical researches testify that nowadays small rural schools as self-evaluating and self-developing systems of educational environment want to keep equilibrium with changeable outside environment. The author diagnosed: 1) new tendencies and priorities of rural schools’ development; 2) both qualitative and quantitative fluctuation in the educational environments of the rural schools; 3) a number of the various models of rural schools’ educational environments. In many rural places the rural school is the only (!) local educational environment therefore it accepts responsibility for not only sustainable self-development, but also for sustainable development of the whole local rural community. The Latvian rural school assumes subsidiary functions, including redress and preventive functions, enlarges target audience. The modern rural school has become an inwardly inclusive environment. It has become a formal and non-formal educational environment for pre-school children, pupils and their families, educators, the whole rural community in the context of life-long and wide-long learning.